The social costs of pesticides: a meta-analysis of the experimental and stated preference literature - Elvia Rufo; Roy Brouwer; Pieter van Beukering (Scientific Reports)
Abstract Pesticide use poses major public health risks and raises environmental concerns globally. We synthesize three decades of stated preferences and experimental approaches that estimate the social costs of pesticide use through consumer and farmer willingness-to-pay (WTP) to prevent or reduce the risks involved. We contribute to the existing literature by demonstrating that the social costs of pesticides vary significantly depending on risk types and levels, where they occur, who is exposed and their risk aversion. The main conclusion is that there exists no single global value estimate for the social costs of pesticide use, there is widespread variation in existing value estimates. Consumers and farmers worldwide share concerns about pesticide risks to their health and the environment. However, there is a need to raise awareness about actual risk exposure levels and public health impacts. Leaving this information out in valuation studies significantly reduces WTP. Equally important is the need to further harmonize stated and revealed preference valuation research design and reporting to facilitate the application of previous study findings to new policy and decision-making contexts.